Early majority engagement pathway best defines transitions from youth to adult elite men's soccer in the UK: A three time-point retrospective and prospective study - Hendry, D. T.; Hodges, N. J. (Psychology of Sport and Exercise, 2018)
Objectives: We evaluated the relative importance of developmental soccer activities engaged in during childhood and adolescence and their relationships with attainment of youth and adult professional status. Design and methods: A mixed retrospective and prospective study was conducted whereby youth academy soccer players in the UK completed demographic and practice history questionnaires at Time 1 (T1; n=102; 13-15yr) and T2 (for those retained on a professional contract at ~17yr; n=26; termed Professional-youth). At T3 (~20yr), players were further differentiated on the basis of progression to adult professional soccer (Adult-professional, n=9; Youth-professional only, n=17). Results: Less than 10% of the sample specialized only in soccer from childhood and no early specializers progressed to Adult-professional. Soccer was the majority sport from early childhood for nearly all players. Players that attained Professional-youth status (T2) accumulated more hours in organized soccer practice during childhood and started in an academy earlier than those that did not. The future adult and youth professionals did not differ on these childhood variables. However, a separate comparison of the professional groups showed that the Adult-Professionals accumulated more hours in play (and proportionately more hours in play) when estimates were based on T1 and T2, than the youth professional. Conclusions: These findings support the early-engagement pathway as a model for successful transitions in professional soccer amongst male youth elite players. This pathway is primarily defined by majority engagement in high volumes of domain specific practice and play in childhood.